Reflexões sobre a pandemia da COVID-19 e pessoas com deficiência/ Reflections on the pandemic of COVID-19 and people with disabilities/ Reflexiones sobre la pandemia de COVID-19 y las personas con discapacidad - Silva Coura, Alexsandro; Silva de Almeida, Isabella Joyce (Journal Health NPEPS, 2020)
Editorial